2017
DOI: 10.1159/000478647
|View full text |Cite
|
Sign up to set email alerts
|

Levistolide A Induces Apoptosis via ROS-Mediated ER Stress Pathway in Colon Cancer Cells

Abstract: Background/Aims: Colorectal cancer (CRC) is one of the leading causes of cancer-related death worldwide. Levistolide A (LA), a natural compound isolated from the traditional Chinese herb Ligusticum chuanxiong Hort, is used for treating cancer. In this study, we investigated the anticancer effect of LA in HCT116 and its isogenic p53-/- colon cancer cells, as well as the underlying mechanisms. Methods: MTT assay was used to evaluate the effect of LA on the viability of cancer cells. Apoptosis and reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 33 publications
(34 reference statements)
2
42
0
Order By: Relevance
“…Increasing intracellular ROS level can induce ER stress and mitochondrial dysfunction, leading to apoptotic cell death in various intestinal cells such as HCT-8, IEC-6 cells and Caco-2 cells. [38,39] High lelvel of CHOP, an ER stress response-related protein, was related to a decrease in antiapoptotic Bcl-2 protein and an increase in a pro-apoptotic Bax protein. [14,16] Rising of Bax/Bcl-2 expression ratio causes the loss of mitochondria membrane permeability (MMP) and disrupts mitochondria function.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing intracellular ROS level can induce ER stress and mitochondrial dysfunction, leading to apoptotic cell death in various intestinal cells such as HCT-8, IEC-6 cells and Caco-2 cells. [38,39] High lelvel of CHOP, an ER stress response-related protein, was related to a decrease in antiapoptotic Bcl-2 protein and an increase in a pro-apoptotic Bax protein. [14,16] Rising of Bax/Bcl-2 expression ratio causes the loss of mitochondria membrane permeability (MMP) and disrupts mitochondria function.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are by-products of oxygen metabolism that occur under cellular oxidative stress conditions and play a critical role in the maintenance of homeostasis [37]. Targeting ROS is an important therapeutic strategy for cancer, as exemplified by cancer drugs [38].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that some natural compounds have an anti‐cancer effect in colon cancer cells. Levistolide A induced apoptosis via the generation of reactive oxygen species and curcumin induced apoptosis via cell cycle arrest in colon cancer cells . Natural compounds have also been used since ancient times for the treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%